Poisoned” khans: the phenomenon of the sudden death of rulers in the mental perception of medieval Mongols - Vorotyntsev L.V.; Galimov T.R. (Золотоордынское обозрение)
Research objectives: To find out the real causes of death of the Mongolian khans Yesugei-baatur, Ogedei, and Guyuk, as well as the circumstances of the emergence of ideas about their poisoning, reflected in a number of narrative sources. Research materials: The work used the Mongolian historical and literary works “Mongol un-niucha tobchiyan” (“The Secret History of the Mongols”) and “Altan Tobchi” (“Golden Legend”), the Mongolian-Chinese dynastic chronicle “Yuan Shi”, as well as the works of the Hulaguid “chroniclers” Rashid al-Din (“Jami at-tawarih”) and Juveini ata-Malik (“Tarikh-i-jehangusha”). In addition, the information contained in the travel notes of the head of the papal embassy to the court of Guyuk Khagan – Giovanni del Plano Carpini – and the ambassador of the French King Louis IX, Guillaume Rubruk, were involved. Results and novelty of the study: the topic of reflection and interpretation in medieval written sources of the sudden deaths of Mongolian rulers has been beyond the attention of nomadic historians up to the present time. Because of this circumstance, the relevance of the problem raised in the study lies in considering one of the least studied aspects of the mental history of Eurasian nomads. The article examines several episodes related to the sudden death of three Mongolian khans (Yesugei-baatur, Ogedei, Guyuk) and the interpretation of these tragic events in narrative sources. Based on a critical analysis of the information presented in written sources, as well as the use of data from natural science disciplines (medicine, geography), the authors conclude that the misconceptions common in historical science about the violent nature of the deaths of the above-mentioned Mongolian rulers are false. According to the authors of the study, the causes of the sudden and premature deaths of Yesugei-baatur, Ogedei, and Guyuk were, respectively, food toxicological poisoning, the consequences of excessive alcohol consumption, and the progressive development of a chronic, incurable disease. It should be noted that the presented work is in the nature of an interdisciplinary study and is a thematic continuation of the article published in the journal “Golden Horde Review” in 2023 [8].